1997
DOI: 10.1093/mnras/284.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an outflow from the Seyfert galaxy NGC

Abstract: New observations using narrow band imaging, long-slit spectroscopy and MERLIN observations of the nuclear region of the Seyfert galaxy NGC 4051 have been made. An edge brightened, triangular region of ionized gas extending 420 pc from the centre of the galaxy has been detected. Long-slit spectra of this ionised gas, taken at 1.5 ′′ from the core, show the [O iii] 5007-Å emission line to consist of two velocity components, both blue-shifted from the systemic radial velocity, with velocity widths of 140 kms −1 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
70
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 26 publications
12
70
0
Order By: Relevance
“…This was also confirmed by the Chandra ACIS-S images of the same galaxy (Uttley et al 1999), which showed a size of the diffuse emission smaller than that of the optical narrow-line regions (30-220 pc, Christopoulou et al 1997), thus implying a clear separation between the X-ray and optical emissions. This is also naturally expected as a consequence of projection effects: as shown by Schmitt et al (2003), who studied a sample of 60 Seyfert galaxies with the Hubble Space Telescope, the Seyfert 1 narrow-line regions objects are more circular and compact than those in the Seyfert 2 galaxies, with the Seyfert 2 subsample characterized by more elongated shapes.…”
Section: Discussionsupporting
confidence: 62%
“…This was also confirmed by the Chandra ACIS-S images of the same galaxy (Uttley et al 1999), which showed a size of the diffuse emission smaller than that of the optical narrow-line regions (30-220 pc, Christopoulou et al 1997), thus implying a clear separation between the X-ray and optical emissions. This is also naturally expected as a consequence of projection effects: as shown by Schmitt et al (2003), who studied a sample of 60 Seyfert galaxies with the Hubble Space Telescope, the Seyfert 1 narrow-line regions objects are more circular and compact than those in the Seyfert 2 galaxies, with the Seyfert 2 subsample characterized by more elongated shapes.…”
Section: Discussionsupporting
confidence: 62%
“…Peterson et al (2000) found that the Balmer lines could arise in a disk-like configuration and the high-ionization lines in an outflowing wind, of which we observe preferentially the near side. The structure and the kinematics of the [O III] lines also suggest an outflow (Christopoulou et al 1997 The X-ray source is variable by at least a factor 30 (Papadakis & Lawrence 1995;Leighly 1999a;Uttley et al 1999;Komossa & Meerschweinchen 2000); long term variations in the average X-ray flux might in principle be caused by absorption by a varying column of material along the line of sight; but this is ruled out by the spectral data; it is the 2-10 keV luminosity which shows large amplitude long-term variations (Uttley et al 1999).…”
Section: Mark 705 (0923+12)mentioning
confidence: 95%
“…It has been known for a long time that the line profiles of the [O iii] doublets show a blue asymmetry with an extended blue wing and a sharp red falloff in a large fraction of AGNs (e.g., Heckman 1981;Whittle 1985;Wilson & Heckman 1985;Grupe et al 1999;Tadhunter et al 2001;Véron-Cetty et al 2001;Zamanov et al 2002;Xu & Komossa 2009;Greene & Ho 2005;de Robertis & Osterbrock 1984;Storchi-Bergmann et al 1992;Arribas et al 1996;Christopoulou et al 1997). The blue asymmetry requires a narrow core Gaussian profile (FWHM ∼ 200-500 km s −1 ) with a blueshifted, broad Gaussian component (FWHM ∼ 500-1000 km s −1 ) to reproduce the observed asymmetric profiles for both [O iii] λλ4959, 5007 emission lines.…”
Section: Introductionmentioning
confidence: 99%